The Role of the State in the Management of Zakat in Indonesia - Hafzi, Ahmad; Ikhwan, Ikhwan; Marneli, Marneli (TAQNIN: Jurnal Syariah dan Hukum, 2024)
Zakat is one of the pillars of Islam that is implemented based on Islamic law. Zakat is not only considered as a ritual worship, but also a social worship that has political aspects due to the involvement of the state in managing it. Since the time of Prophet Muhammad sallallahu "alaihi wa sallam, zakat management has led to a formal, collective, organized, and permanent structure. Zakat management policy develops dynamically along with the development of Islamic territory, economic progress, and government complexity. Zakat management can be done in various ways, and various countries participate in this. Zakat business in Indonesia has also experienced the same development. Zakat has become an integral part of social life in Indonesia, as a country with the largest Muslim majority in the world. The Indonesian state is not an Islamic or religious state, where Islamic sharia is made the cornerstone of the constitution. Rather, it is a democracy that prioritizes religious values. Zakat is mandatory in countries where Islam is the basis of their constitution. Citizens are required to pay zakat, and negligence will be punished. Zakat is part of the state financial system in these countries; it can even be considered a compulsory tax on Muslims as the country does not impose taxes on Muslims except zakat. The author concentrates on the formulation of the problem, "What is the role of the state in the management of Muslims' zakat in Indonesia?" In this paper, the author concludes that, although the payment of zakat in Indonesia is voluntary, the state does not force its citizens to pay it. Instead, the state has a role in the management of zakat as it relates to the public interest where zakat funds are given to Muslims.